Signaling and Screening of Workers' motivation - Josse Delfgaauw; Robert Dur (Center for Economic Studies and ifo Institute (CESifo), 2003)
This paper develops a model in which workers to a certain extent enjoy working. We examine the implications of workers' intrinsic motivation for optimal monetary incentive schemes. We show that motivated workers work harder and, for a given level of e.ort, are willing to work for a lower wage. When people di.er in their motivation to work at a particular firm, the profits of the firm depend on its capability to attract and select highly motivated workers. We show that when the firm has all the bargaining power and workers face application cost, the firm needs to commit to a minimum wage o.er in order to attract workers. A higher minimum wage increases the probability to fill the vacancy, but decreases the expected average quality of job applicants, as it induces lower motivated workers to apply. The optimal level of the minimum wage depends on whether or not the firm can observe the motivation of the applicants. If applicants can credibly signal their motivation, a minimum wage not only helps to attract workers, but also to select the best-motivated worker among the job applicants.
Keywords: 330; signaling and screening models; intrinsic motivation; monetary incentive schemes; wage posting; minimum wage; worker selection